On the taxonomic status of Dina ratschaensis Kobakhidze, 1958 with a description of two new species – Dina imeretiensis sp. nov. and D. samegreloensis sp. nov. (Annelida, Hirudinida: Erpobdellidae) - Clemens Grosser; Shalva Barjadze; Eter Maghradze; Lado Shavadze; Vladimir Pešić; Arnaud Faille (European Journal of Taxonomy, 2023)
Two species of leeches were described from Georgia in the past, Dina ratschaensis Kobakhidze, 1958 from the Racha-Lechkhumi and Kvemo Svaneti region and Trocheta ariescornuta Grosser, Barjadze & Maghradze, 2021 from the Samegrelo-Zemo Svaneti region. Both species were the only known typical representatives of cave leeches in Georgia. Recently, two more species of the genus Dina R. Blanchard, 1894 have been found in karst caves in this country. These leeches are morphologically similar to D. ratschaensis, from which they differ in the shape of the reproductive system, primarily the shape of the cornua of the genital atrium and the shape and extension of the vasa deferentia and ovisacs, justifying the description of two new species, Dina imeretiensis Grosser, Barjadze & Maghradze sp. nov. from the Imereti region and Dina samegreloensis Grosser, Barjadze & Shavadze sp. nov. from the Samegrelo-Zemo Svaneti region. Data on the cave dwelling invertebrate communities in the studied caves are provided. Molecular data are provided, and a phylogenetic tree based on Cox1 sequences of Dina spp. and related genera is provided and discussed.